2021
DOI: 10.1186/s12984-021-00900-9
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in intermuscular coordination underlying isokinetic exercise after a stroke and their implications on neurorehabilitation

Abstract: Background Abnormal intermuscular coordination limits the motor capability of stroke-affected upper limbs. By evaluating the intermuscular coordination in the affected limb under various biomechanical task constraints, the impact of a stroke on motor control can be analyzed and intermuscular coordination-based rehabilitation strategies can be developed. In this study, we investigated upper limb intermuscular coordination after a stroke during isokinetic movements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…[11][12][13][14][15] Rehabilitation approaches should be designed to counteract these maladaptive changes. 16 Currently available rehabilitative BCIs mostly overlook these aspects along with the training protocols, if at all restricting their assessment within the evaluation phases (e.g. to determine efficacy).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Rehabilitation approaches should be designed to counteract these maladaptive changes. 16 Currently available rehabilitative BCIs mostly overlook these aspects along with the training protocols, if at all restricting their assessment within the evaluation phases (e.g. to determine efficacy).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found no consistent pattern of change (e.g., merging or fractionation) observed in the overall composition of the synergy sets. Few studies have characterized the number of muscle synergies after stroke, as compared to unimpaired limbs, as having three different patterns: preservation, merging, and fractionation of unimpaired synergies [ 9 , 18 , 19 ]. More severe impairment after stroke correlated with having fewer synergies (merging) [ 18 , 20 ] or fewer muscle networks [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Human Neuroscience 12 frontiersin.org Seo et al 10.3389/fnhum.2022.937391 The finding on the conservation of altered structure of motor modules throughout the exploratory phases extends the results of our previous work (Roh et al, 2013) that reported the alterations of intermuscular coordination during the stable force generation period only. If the same muscular control under isometric conditions is applied to movement, one can reason that merging or fractionation of motor modules during reaching (Cheung et al, 2012;Park et al, 2021) may also occur from the beginning of a movement, instead of converging to the solution in the middle of a movement.…”
Section: Discussionmentioning
confidence: 99%